DFT Study of Intermolecular Proton Exchange with Some Derivatives of Benzoic Acids - Kurmanova, A.F.; Abilkanova, F.Zh.; Pustolaikina, I.A.; Nikolskiy, S.N. (Karagandy University of the name of acad. E.A. Buketov, 2023)
A theoretical study of proton transfer dynamics in complexes of some substituted benzoic acids with 3,6-ditert- butyl-2-hydroxyphenoxyl (DTBPO) radical is presented. To elucidate the transfer mechanism, reaction pathways for various complexes of benzoic acid derivatives with DTBPO were modeled. The calculations were performed by the DFT method at the UB3LYP/6-31G+(d, p) level of theory using QST3, IRC procedures, in vacuum and toluene medium (PCM solvation model). Geometric and kinetic parameters of complexes with o-, p-, and m-isomers of nitrobenzoic and chlorobenzoic acids were calculated. Theoretically estimated activation barrier of 29-30 kJ/mol turned out to be approximately 30 % higher than the previously obtained experimental data. It was noted that in the case of o-isomers of aromatic acids the coplanarity of the transition state structure is violated, in contrast to the initial state. This leads to a change in the proton transfer mechanism. The dynamics of charge distribution, dipole moment and electrostatic potential in the studied complexes were analyzed. Based on the calculated data, it was shown that the studied intermolecular proton exchange process occurs throughout Hydrogen Atom Transfer (HAT), and not throughout Proton-Coupled Electron Transfer (PCET) mechanism.
Keywords: DFT; spin probe; nitrobenzoic acid; chlorobenzoic acid; 3,6-di-tert.butyl-2-hydroxyphenoxyl; radical; OH-acids; proton exchange; proton transfer; Hydrogen Atom Transfer (HAT)